Renal vascular responses to angiotensin II infusion in two kidneys-one clip hypertensive rats under partial ischemia/reperfusion with and without ischemia preconditioning: the roles of AT1R blockade and co-blockades of AT1R and MasR - Farzaneh Karimi; Mehdi Nematbakhsh (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: The renin-angiotensin system activation, partial ischemia/reperfusion (IR) injury, and hypertension contribute to the development of acute kidney injury. The study aims to look at the vascular responses of angiotensin II (Ang II) during Ang II type 1 receptor (AT1R) blockade (losartan) or co-blockades of AT1R and Mas receptor (A779) in two kidneys one clip (2K1C) hypertensive rats which subjected to partial IR injury with and without ischemia preconditioning (IPC). Experimental approach: Thirty-three 2K1C male Wistar rats with systolic blood pressure ≥ 150 mmHg were divided into three groups of sham, IR, and IPC + IR divided into two sub-groups receiving losartan or losartan + A779. The IR group had 45 min partial kidney ischemia, while the IPC + IR group had two 5 min cycles of partial ischemia followed by 10 min of reperfusion and then 45 min of partial kidney ischemia followed by reperfusion. The sham group was subjected to similar surgical procedures except for IR or IPC. Findings/Results: Ang II increased mean arterial pressure in all the groups, but there were no significant differences between the sub-groups. A significant difference was observed in the renal blood flow response to Ang II between two sub-groups of sham and IR groups treated with AT1R blockade alone or co-blockades of AT1R + A779. Conclusion and implications: These findings demonstrated the significance of AT1R and Mas receptor following partial renal IR in the renal blood flow responses to Ang II in 2K1C hypertensive rats.